Acceptability and Perception of the Vision, Mission and Core Values of the Biliran Province State University - Siat, Gregg O. (Technium Social Sciences Journal, 2021)
The study generally aimed to determine the acceptability and perception among students, faculty, employees, alumni and other stakeholders (parents and partner agency) of the School of Teacher Education of the Biliran Province State University. A descriptive survey method of research was followed involving randomly selected respondents among the different stakeholders of the university. Data were collected using a researcher-made questionnaire which was designed to gather the data needed of the present study. Data were analysed using mean to determine their level of acceptability and perception of the university vision, mission and core values. Results of the study revealed that majority of the respondents were fully accepted the vision, mission and core values of the university. As to the revision, majority of the respondents rated after three years. Furthermore, future research will be conducted in order to increase acceptability among newly and transferee students of the university.